2011
DOI: 10.1159/000329988
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Mineralocorticoid and Glucocorticoid Receptors Reverses Stress-Induced Motor Impairments

Abstract: Aim: Stress and glucocorticoids can influence movement performance and pathologies of the motor system. The classic notion assumes that the glucocorticoid receptor (GR) mediates the majority of stress-induced behavioral changes. Nevertheless, recent findings have attributed a more prominent role to the mineralocorticoid receptor (MR) in modulating behavior. The purpose of this study was to dissociate the impact of MR versus GR activation in movement and stress-associated motor disruption. Methods: Groups of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 149 publications
1
23
0
Order By: Relevance
“…The longitudinal findings revealed that ancestral stress favors precocious onset of elevated motor activity and risk assessment behaviours in response to the novel and slightly aversive environments of open field and elevated plus maze. Both tests are standard assessments of anxiety-like behaviour and response to novelty4344. The indication that ancestral stress enhances the vulnerability to hyperactive and anxiety-like behaviours agrees with findings made in prenatally stressed animals45464748.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The longitudinal findings revealed that ancestral stress favors precocious onset of elevated motor activity and risk assessment behaviours in response to the novel and slightly aversive environments of open field and elevated plus maze. Both tests are standard assessments of anxiety-like behaviour and response to novelty4344. The indication that ancestral stress enhances the vulnerability to hyperactive and anxiety-like behaviours agrees with findings made in prenatally stressed animals45464748.…”
Section: Discussionsupporting
confidence: 80%
“…The open field task allows quantification of exploration of an aversive open arena4344. The open field task was conducted using the VersaMax Legacy Open Field system (Omnitech Electronics, Inc., Dartmouth, NS, Canada; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the data obtained in the present study indicate that locomotor activity was not impaired in DEX-treated mice. Previous studies in rats have shown that DEX significantly decreased movement success as measured by the OF test, with a magnitude similar to stress-induced impairment in animals (Jadavji et al, 2011). Liu et al (2012) tested a rat model of depression elicited by prenatal exposure to DEX, and their results indicate that adult offspring rats exhibited a decreased number of both rearings and distance traveled in the OF.…”
Section: Discussionmentioning
confidence: 88%
“…In this experiment, pregnant rat dams were exposed to a semi-random combination of restraint and swim stress, which may represent an ecologically valid rat model of moderate stress [7],[19] with effects on motor behaviour [21]–[23]. We used the open field task, a standard test to effectively assess motor activity and anxiety-related behaviour [24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The animals were tested using an open field task [22],[23], at P 50, 3 months, 7 months, and 13 months of age. The open field task allows the quantification of motor activity, anxiety-like behaviours, and exploration in an open arena.…”
Section: Methodsmentioning
confidence: 99%